Demand Side Management for Stand-Alone Microgrid Using Coordinated Control of Battery Energy Storage System and Hybrid Renewable Energy Sources. Issue 14 (14th September 2019) - Jha, Sumit Kumar; Kumar, Deepak
Abstract: Distributed generation with battery energy storage (BES) system is an alternative solution for stand-alone AC supply systems. This article addresses the issue of voltage variability of stand-alone microgrid with the adoption of intelligent micro-source controllers. The high energy density of the BES system is used to compensate the voltage fluctuation. A control mechanism is designed to regulate the flow of electrical energy from BES system. The control structure of DC–AC microgrid integrated with BES system is proposed, and the study is extended to explore the mechanism of demand side management (DSM) with the incorporation of voltage-droop characteristics. The BES system is interlinked to maintain the voltage to a desirable range and the proposed work is intended to show the introductory concept on DSM accomplished through voltage-reduction at the consumption-side. The proposed control strategy not only achieves frequency-regulation in adherence to IEEE Standard-1547, but also maintains customers' quality of service while customizing voltage for regulating DSM. The basis of regulating the nickel-metal-hydride battery is state-of-charge of BES system and voltage generated by the hybrid sources consist of photovoltaic and wind energy systems. The adequacy of the proposed control scheme with BES-module is validated using time-domain simulation studies considering voltage-dependent-loads.